2020
DOI: 10.1002/adfm.201910151
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Electroforming Method for Reliable Low‐Power Organic–Inorganic Perovskite Memristors

Abstract: Organic-inorganic hybrid perovskite memristors with high resistiveswitching (RS) reliability and low power consumption are crucial for high-density storage and high-efficiency neuromorphic computing. However, the current overshoot in the electroforming process generally induces overgrowth of conductive filaments (CFs) and degrades the RS performance. Here, a simple photo-assisted electroforming (PAE) method to suppress the current overshoot, in which the visible light irradiation is introduced into the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 47 publications
(68 reference statements)
1
54
0
Order By: Relevance
“…Another possible reason that can lead to 'memristive' behavior, which has to the best of our knowledge not yet been discussed in hybrid perovskites, is the formation of ferroelectric tunneling barriers (Chanthbouala et al, 2012) that remain to be explored. Moreover, light illumination can further suppress and even reverse the resistive switching behavior due to a reduced halide migration barrier ( Figure 2D) (Zhu et al, 2017;Zhao et al, 2020). This opens the possibility of devices that can be set, reset, modified, and read out using a combination of electrical and optical stimuli.…”
Section: Utilizationmentioning
confidence: 99%
“…Another possible reason that can lead to 'memristive' behavior, which has to the best of our knowledge not yet been discussed in hybrid perovskites, is the formation of ferroelectric tunneling barriers (Chanthbouala et al, 2012) that remain to be explored. Moreover, light illumination can further suppress and even reverse the resistive switching behavior due to a reduced halide migration barrier ( Figure 2D) (Zhu et al, 2017;Zhao et al, 2020). This opens the possibility of devices that can be set, reset, modified, and read out using a combination of electrical and optical stimuli.…”
Section: Utilizationmentioning
confidence: 99%
“…Synaptic emulation with ultralow power consumption can be achieved using a low operating current and fast switching. [22][23][24][28][29][30] It is confirmed that I cc reduces to 0.1 µA during the activation process thanks to the ultrathin confined Ag channel, as shown in Figure 2a-(ii), resulting in a low operating current (<1 µA). Furthermore, owing to the low activation barrier of Ag ion migration (<0.2 eV) in Ag-LTA zeolite, [49,50] the pulse width of the synaptic spike reduces from 10 ms to a fast operating speed of 10 ns (see Figure S7 in the Supporting Information).…”
Section: The Development Of Neuromorphic Computation Faces the Apprecmentioning
confidence: 86%
“…[7][8][9][10] Ion drift memristors, which rely on electrochemical metallization (ECM) of the active electrode (e.g., Ag or Cu), have a fast switching speed of tens of nanoseconds. [22][23][24] For a memristive switching mechanism, the morphology modification of conductive filaments (CFs) can generally account for the change in device conductance. [25][26][27] The operating current is mainly determined by the CF dimension, and thin CFs are thus required for ultralow switching power.…”
mentioning
confidence: 99%
“…(30). Here, we keep the system(1) parameters a = 2, b = 8.2, c=5, d = 3, g = 5, r=10000 and set the initial condition (8,3,6,2).Thus, the Lyapunov exponents of system (1) are L1=0.5694, L2=0.0020≈0, L3=-4.9924 and L4=-13.3474, which ensures chaotic properties of the system. Taking smooth function f (t) =sin (2t) as example, the time-domain results of u1, u2, u3, u4 are shown in Fig.…”
Section: )-(F)mentioning
confidence: 99%
“…After that, memristor has attracted researchers more attention all over the world. The memristor is expected to have a wide range of applications thanks to its memory properties, such as information storage [3], neural networks [4], and brain-like computers [5].…”
Section: Introductionmentioning
confidence: 99%